Clinical Pharmacology of Dexamethasone in Infants and Children - Pacifici, Gian Maria (International Journal of Pharmaceutical & Biological Archive, 2023)
Dexamethasone is a potent glucocorticoid and glucocorticoids are used in the treatment of rheumatic disorders, serious inflammatory rheumatic diseases, vasculitis disorders, Wegener granulomatosis, Churg-Strauss syndrome, nephrotic syndrome, bronchial asthma, other pulmonary diseases, Pneumocystis carinii pneumonia, hypoxia, and inflammation of the eye, inflammatory dermatosis, chronic ulcerative colitis, Crohn disease lymphocytic leukemia, bacterial meningitis, cerebral edema associated with parasites and neoplasm. Dexamethasone accelerates the surfactant production in fetal lung, stabilizes liposomal and cell membranes, inhibits complement-induced granulocyte aggregation, improves alveolar-capillary barrier, inhibits prostaglandin and leukocytes production, decreases pulmonary edema, relaxes bronchospasm, and produces hyperglycemia. In infants, dexamethasone is used to treat bacterial meningitis, hypertension, to facilitate extubation, to treat post-intubation laryngeal edema, croup, and surgical stress. In children, dexamethasone is used to suppress inflammation, to treat allergic disorders, croup, bacterial meningitis, and life-threatening cerebral edema. The effects caused by dexamethasone have been reviewed in infants and children. Dexamethasone is metabolized into 6-hydroxy-dexamethasone and this metabolite is further metabolized into different metabolites. The pharmacokinetics of dexamethasone have been studied in infants and children and the mean elimination half-life is 6.81 h in infants and 2.14–3.06 h in children. The prophylaxis, treatment, and trials with dexamethasone have been reviewed in infants and children. Dexamethasone interacts with drugs, treats bacterial meningitis, and is freely transferred across the human placenta. The aim of this study is to review dexamethasone dosing, effects, pharmacokinetics, prophylaxis, treatment, and trials in infants and children, and dexamethasone metabolism, interaction with drugs, treatment of bacterial meningitis, and placental transfer.